2005
DOI: 10.1038/sj.ijo.0802887
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sibutramine on blood pressure: evidence from placebo-controlled trials

Abstract: OBJECTIVE: Sibutramine, a serotonin and norepinephrine transporter inhibitor, is widely used as an adjunctive obesity treatment. There have been concerns that norepinephrine reuptake inhibition with sibutramine could exacerbate arterial hypertension. DESIGN: Combined analysis of two placebo-controlled trials. SUBJECTS: The combined data set consisted of 1336 patients. Of these patients, 966 were randomized to sibutramine and 370 were randomized to placebo. MEASUREMENTS: Body weight, blood pressure, heart rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
2
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 33 publications
(37 reference statements)
2
51
2
2
Order By: Relevance
“…47 However, the authors of a publication that presented the findings from a new metaanalysis of two 12-month sibutramine studies have described a similar small reduction in heart rate in both sibutramine and placebo patients in the subgroups with baseline heart rate X80 bpm. 50 It is interesting to note that the mean baseline heart rate in our study was 79.079.0 bpm. The current Summary of Product Characteristics (SmPC) 14 does not contraindicate the use of sibutramine in patients with well-controlled hypertension, and several studies conducted over the dose range 10-20 mg for periods of upto 12 months have indicated that sibutramine is safe and effective in these patients.…”
Section: Discussionmentioning
confidence: 59%
“…47 However, the authors of a publication that presented the findings from a new metaanalysis of two 12-month sibutramine studies have described a similar small reduction in heart rate in both sibutramine and placebo patients in the subgroups with baseline heart rate X80 bpm. 50 It is interesting to note that the mean baseline heart rate in our study was 79.079.0 bpm. The current Summary of Product Characteristics (SmPC) 14 does not contraindicate the use of sibutramine in patients with well-controlled hypertension, and several studies conducted over the dose range 10-20 mg for periods of upto 12 months have indicated that sibutramine is safe and effective in these patients.…”
Section: Discussionmentioning
confidence: 59%
“…35,36 In contrast to blood pressure however, the overall changes in heart rate seen in the study were approximately twice those reported in other placebo-controlled trials. 21 This difference may relate to gender bias (all subjects in the current study were male) or enhanced sympathetic activity secondary to the combined effects of moderate-severe sleep apnoea 37 and sibutramine. However, the clinical significance of the small heart rate rise observed in this study is not clear despite the known cardiovascular risk associated with an elevated resting heart rate.…”
Section: Discussionmentioning
confidence: 86%
“…While dietinduced weight loss is associated with a fall in blood pressure, 19 the effects from sibutramine are less clear. 20,21 Given that OSA is a risk factor for hypertension 22 and difficult to control blood pressure, 11 there may be specific concerns in using sibutramine in obese patients with OSA. It is possible that sibutramine may initially increase blood pressure in subjects with OSA at least in the early stages of use before weight loss occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Sibutramine increases systolic and diastolic blood pressure by 2-3 and 1-2 mmHg, respectively, and medium heart rate augments by 4-5 beats per minute 17,18 . Anyway, the potential benefits of weight loss outweighed the small increases in heart rate and blood pressure, as shown in the largest study that included 2225 subjects with cardiovascular risk factors, from a primary care setting 19 .…”
Section: Safety and Adverse Eventsmentioning
confidence: 99%